The Effect of TikTok Usage on English Language Proficiency: A Survey-Based Correlational Study - Ilham; Fira; Irwandi (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze the effect of using TikTok as a learning medium on students' English language skills in higher education. Using a quantitative approach and descriptive-correlational survey design, data was collected from 124 active university students from various study programs who use TikTok in their English learning process. The instrument used was a closed-ended questionnaire based on a five-point Likert scale, which measured the intensity of TikTok use (X) and English language skills (Y), including vocabulary acquisition, pronunciation, listening comprehension, and speaking fluency. The statistical analysis showed a very strong correlation between TikTok usage and English language skills, with a correlation coefficient (R) of 0.935. The R Square value of 0.875 indicates that 87.5% of the variability of English skills can be explained by the use of TikTok, while the remaining 12.5% is influenced by other factors. Each one-unit increase in TikTok usage increased English skills by 0.861 units (p < 0.001). The findings suggest that TikTok can be an effective learning media in improving English language skills, especially in vocabulary and listening skills. The practical implication is that educators can utilize this digital platform to support more contextualized and engaging learning.